Regulation of fertilization and early seed development. (20th March 2014) - Dresselhaus, Thomas; Doughty, James
Abstract : Plant reproduction meetings often deal either with pre-fertilization processes such as flowering and pollen biology or post-fertilization processes such as embryogenesis and seed development. The Biochemical Society Focused Meeting entitled 'Regulation of Fertilization and Early Seed Development' was organized to close this gap and to discuss mechanistic similarities and future research directions in the reproductive processes shortly before, during and after fertilization. As an outcome of the workshop, invited speakers and a few selected oral communication presenters contributed focused reviews and technical articles for this issue of Biochemical Society Transactions . We provide here a short overview of the contents and highlights of the various articles.